Stereoselective reduction of 1-benzyl-3,3-dimethyl-5-methylenepyrrolidine-2,4-dione using sodium borohydride with selected metal chlorides - Jumali, Nor Saliyana; Shaameri, Zurina; Mohamad, Hafsah; Hamzah, Ahmad Sazali (Universiti Kebangsaan Malaysia (UKM), 2017)
1-benzyl-3,3-dimethyl-5-methylenepyrrolidine-2,4-dione is an intermediate product produced in the synthesis towards the natural bioactive compound, zopfiellamide A. This compound was synthesized via four main steps including dimethylations, addition with CuBr2, cyclization with benzylamine and reaction with formaldehyde. The corresponding intermediate was an α,ß-unsaturated ketone having exo-alkene group, and it was subjected to reduction using sodium borohydride and selected metal chlorides. In this study, the effect and the hydride transfer mechanism of sodium borohydride-metal chlorides system in the reduction of 1-benzyl-3,3-dimethyl-5-methylenepyrrolidine-2,4-dione was investigated based on the stereochemical outcome of the product.